(untitled) (Al-Academy, 2023)
This research entitled: "Artistic processing of Emotional Scenes in the Narrative Film" deals with how to process and embody those emotional scenes. As there are certain filmic elements that play an effective role in deepening the viewer’s sense of the importance of those scenes, and that their presence in the film is necessary and inevitable, and cannot be dispensed because it forms an interconnected connection with the rest of the film’s scenes, in addition to its dramatic and aesthetic value in the film in crystallizing the viewer’s feelings and integrating him/her into the scene.The research was divided into four chapters, the first chapter includes: the methodological framework, which represented the research problem, and brings the following question: What is the artistic processing of emotional scenes in the narrative film? The aim is to detect artistic processing of emotional scenes in the narrative film. The second chapter, covered theoretical framework. The first topic includes: the concept of emotion and feeling, the second topic: the artistic structure of the romantic scenes. The third chapter includes the research procedures and methodology and its performance, which are the theoretical indicators that come out from the theoretical framework. The research sample has included the narrative film (Malina starring the Italian actress "Monica Bellucci" and "Giuseppe Silvaro") screenplay and directed by "Gio Giuseppe Torrentor Re". The fourth chapter includes analysis and results .